Electronic Science Module in the Merdeka Curriculum: Teacher and Student Perspectives - Ani Setyaningsih; Maryati Maryati; Insih Wilujeng; Arina Zaida Ilma (Jurnal Penelitian Pendidikan IPA, 2023)
Education curriculum in Indonesia changed from the revised 2013 Curriculum to the Merdeka Curriculum. It requires the strategic, methods, teaching materials, learning model, media and method used by teachers. One of the teaching materials is an electronic module. The research aimed to explore information from the perspective of teachers and students regarding the electronic science module in the Merdeka Curriculum. The type of research used is descriptive qualitative and quantitative descriptive. The data collection technique was carried out by interviewing three science teachers, and an open questionnaire of students from three schools in Yogyakarta by 115 students. The research results according to the teacher's and student’s perspective on electronic science module in the Merdeka Curriculum. Teachers are very interested in using electronic modules to help science learning. Students prefer to study with electronic module because they can be accessed via laptops or smartphones and can add teaching materials other than textbooks to the implementation of the Merdeka Curriculum. Electronic module can be used as an alternative solution to support students’ understanding of science material. The results can be used for further research to develop electronic module that are following the characteristics of students and supported by facilities to access it